Seriously Strengthening the Tax-Benefit Link - Pedro Portugal; Pedro Raposo (Institute for the Study of Labor (IZA), 2015)
On January 1st 1994 Portugal introduced, for the first time, inflation indexation in the old-age pension formula. This change considerably decreased the uncertainty regarding the perception of the link between the stream of labor earnings and future pensions. The effect of indexation was large and, by itself, increased the expected pension amount by 28% in real terms. Individuals appear to have reacted to the policy change: labor earnings increase significantly during the eligible years approaching retirement age.
Keywords: J14; J26; J31; 330; pension policy reform; hours; earnings; tax-benefit link